Effect of gamma irradiation on the behavioral properties of crotoxin - Moreira, E. G. [UNESP]; Nascimento, N.; Rosa, G. J. M. [UNESP]; Rogero, J. R.; Vassilieff, V. S. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 1997)
Crotoxin has been detoxified with gamma radiation in order to improve crotalic antiserum production. Nevertheless, present knowledge of the biological characteristics of irradiated crotoxin is insufficient to propose it as an immunizing agent. Crotoxin is known to increase the emotional state of rats and to decrease their exploratory behavior (Moreira EG, Nascimento N, Rosa GJM, Rogero JR and Vassilieff VS (1996) Brazilian Journal of Medical and Biological Research, 29: 629-632). Therefore, we decided 1) to evaluate the effects of crotoxin in the social interaction test, which has been widely used for the evaluation of anxiogenic drugs, and 2) to determine if irradiated crotoxin induces behavioral alterations similar to those of crotoxin in the social interaction, open-field and hole-board tests. Male Wistar rats (180-220 g) were used. Crotoxin (100, 250, and 500 mu g/kg) was injected intraperitoneally 2 h before the social interaction test. Similarly, irradiated crotoxin (2000 Gy gamma radiation from a Co-60 source) was administered at the doses of 100, 250, and 500 mu g/kg for the hole-board test, and at the doses of 1000 and 2500 mu g/kg for the open-field and social interaction tests. ANOVA complemented with the Dunnett test was used for statistical analysis (P<0.05). Crotoxin decreased the social interaction time (s) at the doses of 100, 250 and 500 mu g/kg (means +/- SEM) from 51.6 +/- 4.4 to 32.6 +/- 3.7, 28.0 +/- 3.6 and 31.6 +/- 4.4, respectively. Irradiated crotoxin did not induce behavioral alterations. These results indicate that 1) crotoxin may be an anxiogenic compound, and 2) in contrast to, crotoxin, irradiated crotoxin was unable to induce behavioral alterations, which makes it a promising compound for the production of crotalic antiserum.
Keywords: crotoxin; gamma-irradiated crotoxin; anxiety; social interaction; hole-board test; open-field test